Deciphering the causal landscape: genetic insights into sporadic vestibular schwannoma risk factors through Mendelian Randomization - Yuyang Liu; Hui Feng; Hengchao Ma; Jing Li; Yang Yu; Hua Zhao; Xiaoguang Wang; Yun Li; Jun Zhang; Qi Liu (Discover Oncology)
Abstract Background Sporadic vestibular schwannoma, a benign tumor affecting the vestibulocochlear nerve, poses significant health challenges due to its impact on hearing, balance, and facial nerve function. Despite known associations with genetic mutations and environmental factors, the causality between potential risk factors and sporadic vestibular schwannoma remains underexplored. Objective This study aims to investigate the causal effects of various genetically predicted risk factors on sporadic vestibular schwannoma utilizing a Two-Sample Mendelian Randomization (MR) approach to enhance understanding of its etiology and inform prevention strategies. Methods Leveraging data from genome-wide association studies (GWAS), we analyzed 29 risk factors across five categories: related diseases, lifestyle habits, nutritional status, learning ability, and laboratory indicators. The MR analysis employed instrumental variables (IVs) derived from single nucleotide polymorphisms (SNPs) to assess causal relationships, overcoming traditional observational study limitations. Results Our findings highlight significant associations between sporadic vestibular schwannoma and factors such as ovarian cancer, uterine fibroids and lifestyle habits including dietary intake and alcohol consumption. Notably, higher educational attainment and specific laboratory indicators like high-density lipoprotein (HDL) cholesterol levels were linked to altered disease risk. These results suggest a multifaceted etiology involving hormonal, cardiovascular, gastrointestinal, immune, and metabolic pathways. Conclusion This comprehensive MR study provides novel insights into the diverse risk factors contributing to sporadic vestibular schwannoma, emphasizing the role of genetic predispositions, hormonal influences, and lifestyle choices in its development. The associations identified underscore the need for a multidisciplinary research approach and targeted public health strategies to mitigate sporadic vestibular schwannoma risk. Further research into the underlying mechanisms of these associations is crucial for developing effective interventions and improving patient outcomes.